Factor analysis on hedonic pricing model on open space affecting the housing price in Melaka and Seremban - Asmawi, M. Zainora; Mohit, Mohammad Abdul; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Paiman, Tuminah (Malaysia Institute of Planners, 2018)
Open space near residential area often labelled as development constraint since each residential development must provide 10 percent of open space from the total acreage according to Malaysia planning guidelines. Kuala Lumpur has noticeable lost in open space in residential area and this issue might happen with other neighbourhood states such as Negeri Sembilan and Melaka. Therefore, the purpose of this study is to find the resident perspective on the importance of open space while purchasing their housing property. As such, the aim of the research is to study and examine the characteristics of relationship between public open spaces and residential property value using GIS-Hedonic pricing modelling in the selected residential area in Seremban and Melaka. To find the gist of this study, factor analysis has been used to sum the hedonic pricing model output. It resulted, Seremban and Melaka respondents has chosen the Importance of the House attributes in influencing the house price and Importance of open space following factors in influencing the house price.